Neurological and psychiatric adverse events with prucalopride: case report and possible mechanisms. (25th July 2013) - Carnovale, C.; Pellegrino, P.; Perrone, V.; Antoniazzi, S.; Pozzi, M.; Nisic, A.; Clementi, E.; Radice, S.
Summary: What is known and objective: Chronic constipation is very frequent in the general population. Although usually considered banal, this disorder has considerable personal, social and healthcare impact. Several studies have shown that the psychological impact exceeds that caused by rheumatoid arthritis or haemodialysis. Recently, prucalopride, a highly selective 5‐HT4 receptor agonist has been shown to improve the symptoms of chronic constipation and to have a beneficial effect on social and healthcare impact. The drug was approved by the European Medicine Agency, in 2009 at a dose of 2 mg/day, 'for symptomatic treatment of chronic constipation in women in whom laxatives fail to provide adequate relief'. Neurological side effects or psychiatric disorders have not been reported previously with prucalopride. We present the case of a 61‐year‐old woman, who developed such adverse effects when given prucalopride for the treatment for chronic constipation. Case summary: A few hours after oral administration of this drug at therapeutic dose (2 mg/day), the patient experienced life‐threatening neurological effects that included visual hallucination, loss of balance and memory, disorientation, exhaustion and suicidal ideation. Analysis with the Naranjo algorithm indicated a 'possible' relationship between prucalopride and these disorders. What is new and conclusion: This is the first report of prucalopride‐induced neurological side effects and psychiatric disorders with prucalopride. The absence of other similar reports suggests that prucalopride rarely causes these adverse effects.